2021
DOI: 10.1101/2021.03.20.21254008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring causal relationships between COVID-19 and cardiometabolic disorders: A bi-directional Mendelian randomization study

Abstract: Background: More than 100 million cases of COVID-19 have been reported worldwide. A number of risk factors for infection or severe infection have been identified, however observational studies were subject to confounding bias. In addition, there is still limited knowledge about the complications or medical consequences of the disease. Methods: Here we performed bi-directional Mendelian randomization (MR) analysis to evaluate causal relationships between liability to COVID-19 (and severe/critical infection) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Another study 19 showed that type I error is controlled at the nominal rate when MR is conducted with up to ∼900 SNPs which fell short of genome-wide significance. We have also conducted extensive simulations earlier 20 and have showed that relaxation of the p-value threshold (pthres) up to 0.01 does not lead to increased rate of false positive findings. Based on the above studies and recent advances, here we also considered more liberal pthres for instrument inclusion to improve power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study 19 showed that type I error is controlled at the nominal rate when MR is conducted with up to ∼900 SNPs which fell short of genome-wide significance. We have also conducted extensive simulations earlier 20 and have showed that relaxation of the p-value threshold (pthres) up to 0.01 does not lead to increased rate of false positive findings. Based on the above studies and recent advances, here we also considered more liberal pthres for instrument inclusion to improve power.…”
Section: Methodsmentioning
confidence: 99%
“…There are other limitations of the MR methodology. For more detailed discussions of the strengths and shortcomings of MR, please also refer to other papers 20, 55-57 . For example, horizontal pleiotropy (the instrumental SNP being associated with the outcome via another pathway not through the exposure) may affect the validity of results, which can be accounted for by some MR methods 58, 59 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…While this is an observational study, it is interesting to note that Mendelian randomization studies, which are less prone to confounding, have also shown that COVID-19 may be a causal risk factor for various cardiometabolic and neuropsychiatric disorders 44,45 .…”
Section: Interpretation Of Findings In the Context Of Previous Studiesmentioning
confidence: 99%
“…There have been many retrospective follow-up cohort studies of COVID-19 cases that have generally reported an increase in the severity of existing diabetes and in the incidence of new-onset diabetes in the post-acute phase ( 24 30 ). There has also been a bidirectional Mendelian randomization study that established a potential causal effect of COVID-19 on the subsequent risk of new-onset type 2 diabetes ( 31 ). These reports of new-onset diabetes in the post-acute phase would fall within the WHO definition of long-COVID if the diabetes were a direct consequence of COVID-19.…”
Section: Should New-onset Diabetes Be Considered Among the Many Sympt...mentioning
confidence: 99%